The Relationship Between Nature Relatedness and Psychological Well-Being of Students in Semarang City - Arinda Ayu Cahyandari; Narwastu Krisdiyanto Sejati; Alexander Adi Nugroho Pangestu; Fernandi; Catherine Ananda Setiawan; Bartolomeus Y. Adiwena (Psycho Holistic, 2023)
A natural environment is a place or container where living things are. Many things, including humans, are in the environment and can help living things. For humans, many things can be obtained from the natural environment, including inner peace. This study examines the relationship between Nature Relatedness (NR) and Psychological Well-Being (PWB). This research was conducted using a correlational method and data collection using Google Form. NR is measured using the Relatedness Scale, adapted from the English scale (Nisbet, Zelenski, and Murphy, 2009). Meanwhile, PWB was measured using Ryff's Psychological Well-Being (RPWB) developed by Ryff (1989). This research was conducted using the convenience sampling method on 42 students in Semarang. Testing the hypothesis using Pearson's Product moment correlation analysis shows no significant relationship between NR and PWB (r= 0.201; p>= n.s). Thus, it was concluded that there was no correlation between NR and PWB in students.